AN ANALYSIS OF "ORIFLAME" WOMAN PERFUME ADVERTISEMENTS - Novantia Amandhita Fajar; Nina Setyaningsih (Universitas Dian Nuswantoro, 2015)
Slogan and image usually represent a product in an advertisement. The slogan consists of phrases or sentences, while the image consists of people or else with the background. This research was conducted to find out the tools to convey the message in Oriflame perfume advertisements and to discover the hidden messages by using those tools in the advertisements. Searle’s illocutionary acts theory (1977) and Peirce's semiotics theory (1931) were used as frameworks for analysis. A descriptive qualitative was used to analyze the data. The result shows that from verbal tool analysis, there are 17 illocutionary acts found in the taglines and body copies of the advertisements. The first illocutionary act found in the data is assertive. It is because the advertiser wants their product to be known and to persuade the readers by using information, description, claim, and statement. The second is directive because the advertiser gives command to the readers especially woman to use the perfume. From non verbal tool analysis, the researchers found signs in each background image which then were turned into object and interpretant through a cognition process. From verbal and non verbal tools, the researchers discovered the hidden messages of the Oriflame perfume advertisements. The conclusion is that the advertiser created different images of each advertisement. The images support the tagline and the body copy of advertisement. The advertiser wants the consumers to be able to choose their own perfume based on their characteristics or what they want to be like.